ADDITION OF RICE HUSK NANOCELLULOSE TO THE IMPACT STRENGTH OF RESIN BASE HEAT CURED - Hasran, Muhammad Aditya Ramadhan; Imam, Dian Noviyanti Agus; Sunendar, Bambang (Journal of Vocational Health Studies, 2021)
Background: One of the materials for denture bases is heat-cured acrylic resin (PMMA). This material still lacks impact strength as a mechanical strength property. The addition of reinforcing material is known to increase the mechanical strength of PMMA. One of the reinforcing materials added to PMMA is nano cellulose from rice husks, one of the wastes from agricultural products. Purpose: This study aims to determine rice husk nano cellulose's addition to the PMMA denture base's impact strength. Method:  The research sample consisted of six groups, each group consisting of 8 samples selected by simple random. The PI, P2, P3, P4, P5, and K groups were PMMA with 1%, 2%, 3%, 4%, 5% nano cellulose, and without nano cellulose. Result: Mean impact strength test results were 41.50 x 10-3 ± 3.891 J / mm2 for P1, 44.13 x 10-3 ± 3,980 J / mm2 for P2, 45.63 x 10-3 ± 4,438 J / mm2 for P3, 46.87 x 10-3 ± 4,824 J / mm2 for P4, 49.12 x 10-3 ± 4.016 J / mm2 for P5 and 36.25 x 10-3 ± 1.982 J / mm2 for K. One way Anova test results with p-value of 0.000 indicates differences in the six groups (p<0.05). Conclusion: This study concludes that the impact strength value of PMMA with the addition of rice husk nano cellulose has increased compared to the control group without the addition of rice husk nano cellulose.